2002
DOI: 10.1080/09629350220131962
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine secretion by decidual lymphocytes in transient hypertension of pregnancy and pre‐eclampsia

Abstract: BACKGROUND: Transient hypertension (TH) and preeclampsia (PE) are believed to have different pathophysiology. However, 15-25% of pregnant women initially diagnosed as having TH develop PE. To clarify the immuno-pathogenetical connections between the two syndromes, we studied the pattern of T helper cell (Th)1/Th2 cytokine balance disturbances existing inside maternal decidua in normal pregnancy (NP) and pregnancies complicated with TH and PE. METHODS: Third-trimester decidual tissue was obtained by curettage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 31 publications
5
45
1
Order By: Relevance
“…However, as was shown, RA pregnancies were characterized by low protection which resulted from down-regulated HLA-G molecule [221] and increased expression of classical HLA antigens [217]. Similarly, in PE pregnancies, down-regulation of HLA-G was accompanied by a progressive increase in classical HLA that resulted both from natural trophoblast aging and increased levels of IFN␥ secreted by decidual immunocytes [203,218,219,252]. The sparse presence of anti-HLA antibodies in RA patients resulted probably from the failure to carry gestation long enough to produce response [7].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, as was shown, RA pregnancies were characterized by low protection which resulted from down-regulated HLA-G molecule [221] and increased expression of classical HLA antigens [217]. Similarly, in PE pregnancies, down-regulation of HLA-G was accompanied by a progressive increase in classical HLA that resulted both from natural trophoblast aging and increased levels of IFN␥ secreted by decidual immunocytes [203,218,219,252]. The sparse presence of anti-HLA antibodies in RA patients resulted probably from the failure to carry gestation long enough to produce response [7].…”
Section: Discussionmentioning
confidence: 75%
“…Activated decidual macrophages were also suspected of secreting IL-12, which subsequently increased IFN␥ and IL-2 production by decidual NK and T cells [201,202]. Exceptionally high secretion of IFN␥ with simultaneous low production of IL-10 was found in cultures of mitogen stimulated 3 rd trimester decidual lymphocytes of PE patients [203]. However, some investigators showed that both excessive Th1 and Th2 cytokine serum concentrations were correlated with symptoms of pre-eclampsia [204,205].…”
Section: Cytokines Of Th1/th2 Activity Indoleamine 23 Dioxygenase Amentioning
confidence: 97%
“…It would be of interest to know whether these factors could regulate leptin gene expression in some cell types by activating hypoxia-independent HIF-1 pathways. Interestingly, this could be the case in the hypoxic placenta during preeclampsia, in which increased inflammatory cytokine production has been described (29,30).…”
Section: Effect Of Increasingmentioning
confidence: 99%
“…Interleukin 6 receptor Placentas of preeclamptic patients produce less sIL6R, but more gp130 (IL-6 receptor subunit beta) than placentas of normal pregnant patients (Wilczyński et al, 2002).…”
Section: Il6rmentioning
confidence: 99%